Synced ads: effects of mobile ad size and timing - Brechman, Jean M.; Varan, Duane; Wooley, Brooke; Bellman, Steven (Frontiers in Communication, 2024)
This research was sponsored by a consortium of companies that included Meta, as well as its competitors (e.g., television networks and Google). The authors therefore believe that this balance of interests means that their research is independent, not influenced by any single sponsor or industry group. In addition, SB works for an institute whose corporate sponsors provide funding on the condition that the institute remains completely independent, with written acceptance that sponsors have no influence over data analysis or its interpretation.DV and SB conceived the project, BW supervised development of the experimental stimuli. DV, SB and BW contributed to the experimental design, BW supervised the project. SB analysed the data. JB and SB wrote the paper.